SISTEM PENGENDALIAN PERSEDIAAN BARANG DAGANG PADA KOPERASI KARYAWAN COMFEED MAKMUR SENTOSA PT. JAPFA COMFEED INDONESIA TBK, UNIT BANJARMASIN - Pebriana, Rina; Suasri, Eni; Normini, Normini (Jurnal Riset Akuntansi Politala, 2025)
This study aims to analyze the effectiveness of the inventory control system at Koperasi Karyawan Comfeed Makmur Sentosa (Kopkar CMS), PT Japfa Comfeed Indonesia Tbk, Banjarmasin Unit. Data were collected through observation, interviews, and literature review, and analyzed using a qualitative descriptive approach. The findings indicate that the inventory control system is generally well-implemented, with systematic procedures for receiving, storing, and issuing goods, all recorded through the Web Point of Sales (POS) application, Ketoko. However, discrepancies between system data and physical stock were identified, along with the continued use of the Last In First Out (LIFO) method for product placement. These issues pose potential risks of loss due to product expiration or damage, particularly for fast-moving items..